The experiences, challenges, motivations and coping strategies of informal caregivers in a Grahamstown township - Ntshobane, Zephania Zingqi Zongamele (Rhodes University, Faculty of Humanities, Department of Psychology, 2014)
The health care system in South Africa is currently under strain and it does not cater for everyone's needs. This has left a gap in society whereby you will find that the poor citizens of the country are not being catered for in terms of getting access to adequate healthcare. With this existing gap, there are Non-Governmental Organizations (NGOs) in some of the poor communities in the country. These NGOs have volunteer caregivers who go around the community and taking care of the sick people. Research has often ignored these volunteer caregivers, this current research study investigated the experiences of these volunteer caregivers. The goals of the research study were to investigate the experiences of the caregiver, the motivations of the caregivers and the challenges that they encounter and how they cope with the challenges that arise while performing their caregiving duties. The study was based on the phenomenological paradigm. This paradigm believes that the subjective experience of the individual is an essential source of information. In-depth interviews were conducted with the four participants who took part in the study. An interview guide was utilised to help guide the interview process. Interpretive Phenomenological Analysis (IPA) was used in analysing the data. IPA is a way of analysing data, which investigates how a person, in a given setting understands an experience. The findings showed that the caregivers had both negative and positive experiences. They experienced the care recipients as being appreciative of them. However, they experienced the family members of the care recipients as being uncaring; financial constraints were also a negative experience. Several challenges were stated by the participants, including a lack of government support, alcohol abuse by the care recipients and challenging working conditions. The participants were motivated to volunteer as caregivers by a number of things. Altruistic motivation was the first, which included the love for the community and the poverty in the community. Reciprocity was another motivating factor, as well as religious duty and career advancement. In this research study there was one coping strategy that came out; the participants stated that they seek advice and consult with someone or go for supervision within the organization when they are faced with a difficult situation. The findings in the research study were similar to those found in previous research. One notably different finding was that in previous research, the caregivers have been found to abuse alcohol in order to cope with stress. However, in this research study, the care recipients are the ones who are abusing alcohol. The research recommends that the government assists the informal caregivers, either financially or with infrastructure.
Keywords: Caregivers -- South Africa -- Grahamstown; Caregivers -- Psychology; Volunteers -- South Africa -- Grahamstown; Voluntarism -- Psychological aspects; Adjustment (Psychology)